Chinese Minority Perceives the Doctor-Patient Relationship Differently: A Cultural and Economic Interpretation - Yang, Qian; Zhang, Hao; Yu, Mengfei; Hu, Xiaoqian; Gu, Yuxuan; Sun, Xueshan; Zhen, Xuemei; Gu, Shuyan; Huang, Minzhuo; Wei, Jingming; Zeng, Yuhang; Dong, Hengjin (Frontiers in Public Health, 2019)
In China, doctor-patient relationships (D-P relationships) are cited frequently and attracted international attention. This study assesses whether the D-P relationship experienced by the Chinese is associated with ethnicity, hospital hierarchies, and socioeconomic factors. In a national cross-sectional survey, multi-stage random sampling was adopted to assess regional and socio-economic differences between year 2016 and year 2017. Each area surveyed consisted of about 250 randomly chosen households, and valid results were obtained from 4173 adults aged 16–99. When provided a choice of eight types of D-P relationship, for doctors in primary care institutions, 63.8% of ethnic minorities indicated having a friend-type relationship with their physicians, with 23.3% having a trading/reciprocal relationship. Han Chinese, however, predicts the opposite relationship between doctors from different hierarchy and the types of D-P relationship. For physicians working in hospitals, this difference in relationship was more pronounced, where 52.9% of ethnic minorities indicated having a friend-type relationship with their physicians, and 30.1% indicated the presence of a trading/reciprocal relationship. For Han Chinese, however, 53.3% indicated having a reciprocal relationship with their doctor. Overall, the prevalence of friendly D-P relationships werewas correlated with ethnic minorities, lower levels of education, and lower incomes. Ethnic minorities are most likely to perceive their physicians as friends, while Han Chinese are more likely to perceive a trading relationship with their physicians. The primary contribution of this research is the finding that D-P relationships differ for Han Chinese and other ethnic minorities.